املدخل إىل دراسة الفقه اإلسالمي - Md. Sawari, Mohd. Fuad (IIUM Presss, 2021)
The book provides an introduction to the science of Islamic jurisprudence, stating the basic concepts of Islamic jurisprudence through discussions of the concept of Shariah and jurisprudence, the objectives of Shariah, the general characteristics of Islamic law, and the history of Islamic legislation and jurisprudence. This book deals with the rules of jurisprudence by talking about the concept of jurisprudential rules and the history of their inception and development, and presenting the five general rules. These topics were presented in a simple and easy-to-deal manner, sometimes accompanied by tables and drawings that were almost absent in the writings of the ancients and contemporaries, in order to bring the reader closer to the intended meaning, mentioning the Qur’anic verses and the hadiths of the Prophet as a problem, which may help the reader to read and memorize them.